2008
DOI: 10.1002/smi.1231
|View full text |Cite
|
Sign up to set email alerts
|

Sources of stress and coping strategies of US soccer officials

Abstract: Stress from officiating has been found to have a profound impact on official's mental health, attentional focus, performance, satisfaction with their profession and dropout intentions. Although some studies have been conducted regarding the frequency and intensity of the major sources of stress experienced by sport officials, no research has attempted to determine how sport officials cope or attempt to cope with these stressors. Through a national soccer official organization, questionnaire packets were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
19

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 18 publications
0
44
0
19
Order By: Relevance
“…As found in previous research (e.g., Mathers & Brodie, 2011;Voight, 2009;Wolfson & Neave, 2007) the rugby union referees adopted various problem-and emotion-coping strategies during performance to manage successfully the stressors and emotional response encountered. This included proactive-coping and informational social support (from mentors, experts and sport psychologists) prior to games; acceptance, ownership, task / process focus and emotion-focused coping during games; and finally, guided reflective practice post-game.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As found in previous research (e.g., Mathers & Brodie, 2011;Voight, 2009;Wolfson & Neave, 2007) the rugby union referees adopted various problem-and emotion-coping strategies during performance to manage successfully the stressors and emotional response encountered. This included proactive-coping and informational social support (from mentors, experts and sport psychologists) prior to games; acceptance, ownership, task / process focus and emotion-focused coping during games; and finally, guided reflective practice post-game.…”
Section: Discussionmentioning
confidence: 52%
“…Although a number of studies (e.g., Neil et al, 2013;Voight, 2009) have identified time pressures (conflict between demands of family life and officiating), fear of physical harm, and the crowd as stressors that affect referees, they were not found within this study. This is likely due to the professional context in which the participants worked.…”
Section: Discussionmentioning
confidence: 67%
“…While the investigation of these factors has been useful in identifying coping strategies that may lead to improved illness outcomes and increased functioning in the chronically ill, the literature has been criticized for an over-reliance on dispositional coping strategies. The adoption of more specifi c, acute coping measures that may interact with generalized coping strategies is therefore advocated (Coyne & Racioppo, 2000;Voight, 2009). …”
Section: Copingmentioning
confidence: 99%
“…No que diz respeito à análise deste constructo psicológico, os árbitros têm recebido menor atenção nas investigações sobre os fatores causadores de estresse em suas atividades laborais esportivas quando comparados a atletas e treinadores (ANSHEL; KANG;JUBENVILLE, 2013 PORTER, 1997, MIRJAMALI et al, 2012TSORBATZOUDIS et al, 2005;VOIGHT, 2009).…”
Section: Introductionunclassified
“…Dentre os estudos que analisaram fatores estressantes na arbitragem esportiva, é possível notar que a maioria investigou árbitros de modalidades coletivas, como basquete (ANSHEL; WEINBERG, 1996; KAISSIDIS-RODAFINOS; ANSHEL; PORTER, 1997;MIRJAMALI et al, 2012;ROSE JÚNIOR;LEMOS, 2002;SILVA et al, 2010;STEWART et al, 2004), futebol GENCAY, 2009;MIRJAMALI et al, 2012;VOIGHT, 2009), futsal (FERREIRA et al, 2009), handebol (MIRJAMALI et al, 2012TSORBATZOUDIS et al, 2005), vôlei (MIRJAMALI et al, 2012;SILVA et al, 2010;ELLERY, 1994), hóquei (DORSCH;PASKEVICH, 2007), rugby (RAINEY; HARDY, 1999) e beisebol (RAINEY, 1995). Observa-se que em todos os estudos supracitados a análise do estresse em árbitros não direciona o seu foco investigativo para os esportes individuais como, por exemplo, as ginásticas.…”
Section: Introductionunclassified